ÌâÄ¿ÄÚÈÝ
ÉèÊýÁÐ{an}µÄÇ°nÏîºÍΪSn£¬Èô¶ÔÓÚÈÎÒâµÄn¡ÊN*,¶¼ÓÐSn=2an-3n,(1)ÇóÊýÁÐ{an}µÄÊ×ÏîÓëµÝÍƹØϵʽan+1=f(an);
(2)ÏÈÔĶÁÏÂÃ涨Àí£¬ÈôÊýÁÐ{an}ÓеÝÍƹØϵan+1=Aan+B,ÆäÖÐA¡¢BΪ³£Êý£¬ÇÒA¡Ù1,B¡Ù0,ÔòÊýÁÐ{an-}ÊÇÒÔAΪ¹«±ÈµÄµÈ±ÈÊýÁУ¬ÇëÄãÔÚµÚ£¨1£©ÌâµÄ»ù´¡ÉÏÓ¦Óñ¾¶¨Àí£¬ÇóÊýÁÐ{an}µÄͨÏʽ;
(3)ÇóÊýÁÐ{an}µÄÇ°nÏîºÍSn.
½âÎö£º(1)¡ßSn=2an-3n,
¡àSn+1=2an+1-3(n+1).
¡àan+1=Sn+1-Sn=2an+1-2an-3.
¹Êan+1=f(an)=2an+3.
(2)¡ßan+1+3=2(an+3),
¡à{an+3}ΪµÈ±ÈÊýÁУ¬Ê×ÏîΪa1+3=6,¹«±ÈΪ2£¬¹Êan+3=6¡Á2n-1=3¡Á2n.
¡àan=3¡Á2n-3.
(3)Sn=a1+a2+a3+¡+an
=3(2+22+¡+2n)-3n
=3¡Á2n+1-6-3n.
![](http://thumb.zyjl.cn/images/loading.gif)
Á·Ï°²áϵÁдð°¸
Ïà¹ØÌâÄ¿